Islamic Religious Education Teachers’ Perceptions of Emancipated Learning Curriculum in Pontianak City - Aziz, Abdul; Budiono, Budiono (Yayasan Rahmat Islamiyah, 2024)
The Emancipated Learning Curriculum, introduced in 2019 under the leadership of the Minister of Education and Culture, Nadiem Makarim, stands as the latest curriculum initiative in Indonesia, evolving from the 2013 curriculum. While some teachers express appreciation for the curriculum policy, others harbor objections based on various considerations. The changes in the curriculum are perceived as adjustments to various components that support learning. To delve into these dynamics, the research addresses the following questions: 1) What are the teachers’ perceptions of the concept of the emancipated learning curriculum?; 2) What are the teachers’ perceptions of the emancipated learning curriculum policy?; and 3) What are the teachers’ perceptions of the implementation of the emancipated learning curriculum? Employing a mixed methods approach, this research used the phenomenological method. Data were collected through questionnaires and interviews simultaneously, and a concurrent triangulation strategy was employed for data analysis. This involved the simultaneous collection of quantitative and qualitative data, enabling the comparison of the two types of data for convergence, differences, and synthesis. The findings of the research show that teachers’ perceptions of the emancipated learning curriculum are generally positive. Specific details include: Teachers’ perceptions of the concept of the emancipated learning curriculum fall within the good category, accounting for 61.11%. The evaluation of teachers’ perceptions of the emancipated learning curriculum policy reveals a positive outlook, with 83.33% rating it as good. Additionally, 72.22% of teachers express a positive perception of the implementation of the emancipated learning curriculum.